Encyclopedia of human relationships - Reis, Harry T.; Sprecher, Susan 1955-; Gale Group (Thousand Oaks, Calif. Sage Publications, 2009)
Offers an interdisciplinary view of all types of human associations. Provides a state-of-the-art review of the extensive theories, concepts, and empirical findings about human relationships.
Volume 1. List of entries -- Reader's guide -- About the editors -- Contributors -- Introduction -- Entries -- A - E -- Volume 2. List of Entries -- Entries -- F - O -- Volume 3 List of Entries -- Entries -- P - W -- Index.
Electronic reproduction.
Keywords: Interpersonal relations -- Encyclopedias; Social interaction -- Encyclopedias; Electronic books